The translation of women within the context of the Ottoman-Turkish women's movement (1868-1935) - Avci Solmaz, Safiye Gul; Karadag, Ayse Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
The Ottoman Muslim and Turkish women's movement provides a unique study field for researchers to follow the traces of women's change and the reconstruction of gender roles during the modernisation process initiated in the Ottoman Empire and continued in the transition period from a centuries-old empire to a nation-state, the Turkish Republic. It also sets a perfect example in terms of demonstrating how feminism can acquire different meanings when translated into different contexts. The article aims to approach the movement from the perspective of translation studies and views the change of women and their gender roles as a translation process. Investigating the translation of women within the relevant socio-cultural and political context based on two concepts of translation studies, rewriting and self-translation, the study suggests that women followed purposeful translation strategies in this process to expand their agency and authority in a patriarchal society over time. Presenting a short historical background of the movement with a discussion on women's agency through two strategies, the act of translation and gradualism, the article assesses the dynamics of the movement through the example of Seniha Sami Morali, an underrepresented woman and translator in history, who experienced the process firsthand.
Keywords: Gender studies; translation studies; Ottoman-Turkish women's movement; self-translation; rewriting; gradualism; women translators; Seniha Sami Morali; GENDER; History